The course and determinants of post-traumatic stress over 12 months after hospitalization for COVID-19 - Knut Stavem; Knut Stavem; Knut Stavem; Trond Heir; Trond Heir; Toril Dammen; Toril Dammen; Eivind Brønstad; Eivind Brønstad; Tøri Vigeland Lerum; Tøri Vigeland Lerum; Michael T. Durheim; et al. (Frontiers in Psychiatry, 2022)
ObjectiveTo assess the trajectory of symptoms and symptom-defined post-traumatic stress disorder (PTSD) from 1.5 to 12 months after hospitalization for COVID-19 and determine risk factors for persistent symptoms and PTSD.MethodsThis was a prospective cohort study of consecutive patients discharged after hospitalization for COVID-19 before 1 June 2020 in six hospitals in Southern Norway. Symptom-defined PTSD was assessed by the post-traumatic stress disorder (PTSD) checklist for DSM-5 (PCL-5) at 1.5, 3 and/or 12 months after hospitalization, using DSM-5 criteria. Changes in PCL-5 symptom score and the prevalence of PTSD were analyzed with multivariable mixed models.ResultsIn total, 388 patients were discharged alive, and 251 (65%) participated. Respondents had a mean (SD) age of 58.4 (14.2) years, and 142 (57%) were males. The prevalence of symptom-defined PTSD was 14, 8, and 9% at 1.5, 3, and 12 months, respectively. WHO disease severity for COVID-19 was not associated with PCL-5 scores. Female sex, lower age and non-Norwegian origin were associated with higher PCL-5 scores. The odds ratio (OR) (95%CI) for PTSD was 0.32 (0.12 to 0.83, p = 0.019) at 3 months and 0.38 (0.15 to 0.95, p = 0.039) at 12 months compared to 1.5 months. There was no association between PTSD and WHO severity rating.ConclusionsThe level of PTSD symptoms decreased from 1.5 to 3 months after hospitalization, but did not decrease further to 12 months, and there was no association between PTSD symptoms and COVID-19 disease severity.